2013
DOI: 10.1111/iwj.12100
|View full text |Cite
|
Sign up to set email alerts
|

Wound assessment tools and nurses' needs: an evaluation study

Abstract: The purpose of this study was to ascertain how well different wound assessment tools meet the needs of nurses in carrying out general wound assessment and whether current tools are fit for purpose. The methodology employed was evaluation research. In order to conduct the evaluation, a literature review was undertaken to identify the criteria of an optimal wound assessment tool which would meet nurses' needs. Several freely available wound assessment tools were selected based on predetermined inclusion and excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 24 publications
1
39
1
3
Order By: Relevance
“…A assistência ao paciente com feridas deve ser baseada em um cuidado integral e a avaliação da ferida é parte fundamental desse processo (19) . Para nortear os profissionais na avaliação, são fundamentais a utilização de instrumentos que lhes fornecerão subsídios no tratamento de feridas e a escolha do agente terapêutico adequado, além de possibilitar o acompanhamento da evolução da lesão durante todo o processo de reparação tecidual em cada fase da cicatrização (20) .…”
Section: Idiscussãounclassified
“…A assistência ao paciente com feridas deve ser baseada em um cuidado integral e a avaliação da ferida é parte fundamental desse processo (19) . Para nortear os profissionais na avaliação, são fundamentais a utilização de instrumentos que lhes fornecerão subsídios no tratamento de feridas e a escolha do agente terapêutico adequado, além de possibilitar o acompanhamento da evolução da lesão durante todo o processo de reparação tecidual em cada fase da cicatrização (20) .…”
Section: Idiscussãounclassified
“…As a result of the global increase in chronic disease due to population ageing (Dall et al 2013, Wu et al 2013, it is foreseeable that there will be a concomitant increase in the number of people with wounds secondary to chronic disease. An important component of wound care management involves regular wound assessments to monitor healing progress (Greatrex-White & Moxey 2015). Using validated instruments to perform and record wound care assessments helps to provide a more standardized method for documentation and communication of the wound condition between healthcare providers and over time (Mullins et al 2005, Arndt & Kelechi 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a community-based multidisciplinary team approach has been widely adopted for delivery of wound care services (Abrahamyan et al 2015). A generic and easy-to-use wound assessment instrument that is applicable to a variety of wound types would be a useful tool enabling multidisciplinary wound care teams to assess and compare wounds more efficiently (Greatrex-White & Moxey 2015). This is particularly relevant for wound care management delivered in primary care and community settings, where wound care providers often encounter patients with diverse wound types that may range from acute post-surgical wounds to chronic ulcers (Friman et al 2011, Dutton et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more and more patients with wounds need wound management in the community setting. 13 The nursing activities for patients with VLUs in various institutions cannot reach unitary quality due to the limitations of skills and methods. The status quo of wound care has reported that the demand of advanced practice nurses exceeds supply.…”
mentioning
confidence: 99%
“…By providing a nursing program for clinical nurses to follow, which can lead to faster wound healing, a reduction in complications, shorter patient stay, and finally improved quality of care that results in reduced costs are observed. 13 The use of standardized nursing terminology will also promote nursing practice and drive nursing revolution.…”
mentioning
confidence: 99%